1994
DOI: 10.1007/bf00316959
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water availability on the phenotypic expression of herbivore resistance in northern red oak seedlings (Quercus rubra L.)

Abstract: The phenotypic expression of quantitative characters is a function of the individual's genotype and the environment in which it is measured. In a previous reciprocal transplant study, we found that patterns of genetic differences in resistance to herbivores among adjacent subpopulations of northern red oak (Quercus rubra L.), were consistent with a local adaptation hypothesis. The goal of this study was to determine if variation in water availability may have been a mechanism responsible for these previously o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Further, naturalized populations of B. rapa exhibit significant additive genetic variation for foliar glucosinolate content Mitchell-Olds 1996, 1998;Siemens et al 2002), suggesting that the lack of additive genetic variation in foliar glucosinolate content in this species is not a factor that constrains the evolution of this trait. It is also important to note that the finding of significant additive genetic variation in defensive traits is not uncommon (Berenbaum et al 1986;Marquis 1990Marquis , 1992Simms and Rausher 1989;Sork et al 1993;Schemske 1993, 1994;Han and Lincoln 1994;Stowe et al 1994;Sagers and Coley 1995;Siemens et al 2002;Alves et al 2007;Andrew et al 2007; but see Núñez-Farfán and Dirzo 1994).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Further, naturalized populations of B. rapa exhibit significant additive genetic variation for foliar glucosinolate content Mitchell-Olds 1996, 1998;Siemens et al 2002), suggesting that the lack of additive genetic variation in foliar glucosinolate content in this species is not a factor that constrains the evolution of this trait. It is also important to note that the finding of significant additive genetic variation in defensive traits is not uncommon (Berenbaum et al 1986;Marquis 1990Marquis , 1992Simms and Rausher 1989;Sork et al 1993;Schemske 1993, 1994;Han and Lincoln 1994;Stowe et al 1994;Sagers and Coley 1995;Siemens et al 2002;Alves et al 2007;Andrew et al 2007; but see Núñez-Farfán and Dirzo 1994).…”
Section: Discussionmentioning
confidence: 98%
“…Typically, studies that have investigated plant defense against insect herbivores demonstrate significant genetic variation in defense (Berenbaum et al 1986;Simms and Rausher 1989;Marquis 1990Marquis , 1992Sork et al 1993;Schemske 1993, 1994;Han and Lincoln 1994;Stowe et al 1994;Sagers and Coley 1995;Siemens et al 2002;Alves et al 2007;Andrew et al 2007; but see Núñez-Farfán and Dirzo 1994). As such, the evolutionary response of defense to herbivore-imposed selection does not appear to be limited by a lack of genetic variation in defense.…”
Section: Introductionmentioning
confidence: 96%
“…Earlier studies had indi-cated that drought stress often makes plants more sensitive to insect damage. Its effects may increase herbivory because of an increasing concentration of foliar nutrients and soluble carbohydrates (STOWE et al 1994). Herbivory may be also influenced by other host plants nearby, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The intensity of insect damage was found to be correlated with rainfall. Earlier studies had indicated that drought stress often makes plants more palatable to herbivores and more sensitive to insect damage (Stowe et al 1994). The effect of drought stress on the sensitivity of plants to insect damage has been cited by many authors (e.g.…”
Section: Insect Feedingmentioning
confidence: 99%